Penile enhancement: A comprehensive and current perspective - Yuan Chen; Yinuo Jiang; Xiao Li; Bin Wang; Xiaofeng Guo; Zihang Mai; Weifen Deng; Yuanchang Zhu; Baoquan Han; Zhongyi Sun (Current Urology)
Abstract. An increasing number of men with healthy and normal penises want to enlarge their penis. Therefore, this review evaluated the mental health status of men who complained of a small penis and examined the state of nonsurgical and surgical treatments for male patients seeking penile enlargement, along with a risk assessment for each. Various medical, tractional, injectable, and surgical modalities have been investigated for penile augmentation. However, the development of new products and surgical techniques, such as Penuma, and tissue engineering may yield fewer complications, good operative effects, shorter operative times, and high patient satisfaction, bringing hope to patients interested in penile enlargement.